Post Harvest and Technology of Watermelon (Citrullus lanatus) Plants in Integrated Field Laboratory Faculty of Agriculture Kediri - Nunuk Helilusiatiningsih; Sumarji; Pamuji Setyo Utomo (Formosa Journal of Applied Sciences, 2022)
Post- haverst important to study because commodities were living materials that were easily damaged after being harvested. The purpose of the experiment was to analyze the post-harvest quality of watermelon at the integrated field laboratory in Kediri. The research method uses organoleptic tests which include taste, color, type, shape, fruit weight. Two types of watermelon were analyzed, namely Samara watermelon (non-seed) and Black sweet. The results showed that the fruit with the heaviest weight was the Samara watermelon, which was 5.27 kg/fruit, red in color, artificial and non-seeded, compared to the black sweet, which weighed around 4.52 kg/fruit. The organoleptic test of samara watermelon was that the taste, type, color were very popular with consumers while the round shape was favored by consumers. Black sweet watermelon based on sensory test of taste was very preferred, yellow color was very preferred, oval shape and the type is liked by consumers. The profit from the samara watermelon harvest was Rp. 3.7 million and black sweet Rp. 3.2 million